Architecture of methodological approaches in the management of receivables and accounts payable of an agricultural organization of the fisheries complex of the region - Lysenko Yu.V.; Ovsyanitskaya L. Y.; Lysenko M.V.; Filipsonova E. N. (BIO Web of Conferences)
The survival and sustained success of any agricultural organization hinges on a fundamental pillar: financial stability. This isn't simply about having enough money to operate; it's about building a resilient system that can weather unpredictable market fluctuations, volatile commodity prices, and unforeseen natural disasters. A financially robust agricultural organization operates with a degree of independence from market whims, decreasing its vulnerability to financial hardship and the ever-present threat of bankruptcy. This research delves into the critical importance of a holistic and scientific approach to analyzing key financial indicators within agricultural organizations. Such an approach goes beyond simply reviewing financial statements; it involves a nuanced understanding of the underlying factors that influence those indicators. For instance, examining the effectiveness of managing receivables and payables offers valuable insights into an organization's cash flow management practices and its ability to meet its financial obligations. To gain tangible insights into the financial health of agricultural organizations, this research utilizes the annual accounting (financial) statements of a fishery complex from 2020- 2022. Analyzing these statements allows for the assessment of key financial ratios, trends in revenue and expenditure, and the overall efficiency of operations. By applying these recommendations, agricultural organizations can strengthen their financial foundations, improve their resilience, and ultimately achieve greater long-term success in the face of an increasingly challenging agricultural landscape.